Review paperThe use of deep friction massage with olive oil as a means of prevention and treatment of sports injuries in ancient times - Nomikos, Nikitas N.; Nomikos, George N.; Kores, Demetrios S. (Archives of Medical Science, 2010)
The aim of this research was to analyse the use of olive oil as a means of prevention and treatment of sports injuries in the ancient world. The method adopted was based on a thorough study of Greek and world literature. Writings of major ancient philosophers and physicians such as Hippocrates, Aristotle, Philostratus, and Lucian have been analysed in depth. According to the results, the use of massage, together with olive oil rub, helped to reduce muscle fatigue, to remove lactic acid, and to prevent the occurrence of sports injuries through flexibility provided to the skin of athletes. The therapeutic use of oil in the ancient world was fully recognized; and as a result Athenian athlothetes (sponsors of sporting events) provided free oil to all sport facilities where athletes could make free use of it [1].